Trends in Microbiology 2024 - Pabulo Henrique Rampelotto; Milan Kolář (Life)
Microbiology is a key component of modern science, significantly influencing various fields, such as agriculture, medicine, and environmental management, particularly through the One Health approach, which recognizes the interconnectedness of human, animal, and environmental health [...]